COMPARATIVE OF AGROECOLOGICALLY FERTILIZERS WITH MINERAL FERTILIZER IN SECOND CUT SUGARCANE IN THE REGION OF THE SOUTHWEST STATE OF GOIÃS, BRAZIL - Almeida JÃºnior, Joaquim JÃºlio; Silva, Danubio Deikti Rodrigues; Lazarini, Edson; Smiljanic, Katya Bonfim Ataides; Matos, Francisco Solano AraÃºjo; Barbosa, Uessiley Ribeiro; Silva, Victor JÃºlio Almeida; Miranda, Beatriz Campos; da Silva, Reinaldo Ferreira; de Almeida, Eder Vaz; Leal, Adriano Bernardo; de Rezende JÃºnior, Vilmar Neves (REVISTA DE AGRICULTURA, 2020)
This work evaluated the second cut of the technological variables "plant biometrics" of sugarcane culture using different fertilizers and different doses of organomineral fertilizers in the southwestern region of GoiÃ¡s, Brazil. The experiment was conducted in the 2017/2018 harvest, in Mineiros, state of GoiÃ¡s, Brazil. Initial and final plant population, tons of cane per hectare, total recovered sugar, plant height, stalk diameter, and internodes number were evaluated. There were eight procedures with three different dosages of organominerals, three dosages of poultry beds, one chemical fertilizer, and control distributed in randomized blocks with four repetitions. It can be concluded that the poultry bed is excellent for keeping technological variables tested in the best achieved means, with the two main parameters tons of cane per hectare (TCH) and total recovered sugar (TRS) being statistically equal when compared to mineral fertilizer.